Addressing Information Gaps - Mulder, Christian (IMF Staff Position Notes; Staff Position Note ;, 2009)
This paper outlines some of the key information gaps in the information used in the assessment of financial institution and financial system stability and the priorities for filling them. Key areas for attention include the granularity of disclosures on exposures by large and complex financial institutions; disclosures and assessments of complex structured products; revamping of indicators used in financial stability analysis to focus on indicators with greater early warning content; and improving transparency in over-the-counter derivatives markets. Recommendations have been made by several institutions and forums to address gaps in information that contributed to the crisis. One of the key recommendations is to adopt good practices for disclosures by banks on activities affected by the financial turmoil, including meaningful information on exposures and impacts, with appropriate levels of granularity. It is imperative to strengthen public disclosure practices of systemically important financial institutions by making reporting information more granular and consist.